Migrações, negociações espaciais e a dinâmica demográfica de Valparaíso de Goiás GO: rupturas e continuidades - Silva, Gilmar Elias Rodrigues da (2017)
The political and socioeconomic transformations in Brazil and the state of Goiás in the last decades are witnesses and justify the regional dynamics and as mobilities. In this sense, it is ensured that there are attractive spaces for the migrants, while others can not be used. The conformation of Valparaiso de Goiás is due to the phenomenon. This place in the municipality in the contiguous with the Distrito Federal and characterizes it as attractive for the dwelling. In this overlay, spaces such as space, time and migration emerge as input. These are a possibility of understanding the process of contemporary urbanization in the state of Goiás and in the Metropolitan Area of Brasília-AMB. The impulses for the metropolization of the area of communication concentrate on the spatiality of capital. This migration and impact on the subjects in agreement agency. That is, to the extent that capital and, along with it, the jobs migrate, the subject is urged to migrate. The materialization of existence in the space of disputes requires a strategy elaboration that enables the nascent way of life. Like the definition of "space negotiations". In the warp you see negotiations, the subject engages the knowledge acquired in his past experience. These can be associated, directly or through archetypes, to a rural existence. Asymmetric, post-actualized in the present life, it is not a city space to cultivate factors of persistence and/or permanence of the rural life in the context of Brazilian and Goian urbanization. These elements result in difficulties for an appropriation of the urban space and for a materialization of life. Thus, it becomes relevant to know the conflicts of the apparent "slow life" left in the act of migrating in search of the possibility of a better life in the city, a nervous life. This confrontation highlights an invention of the inhabitants of Valparaiso de Goiás for a spatial negotiation interconnected by experiences of previous reminiscences as a strategy to live together in the city in contemporary times. In these conditions of coexistence, rural and urban ways of life are amalgamated in the fabric of metropolitan life. It is concluded that, due to the fact that a modern life experience has been extended in rural areas - the advent of urbanization in Brazil is recent - by the effective migration dynamics in national, regional and local territory, by the condition of birth From the city; The subjects that live there are not functional or mature to manage life in this urban space.